Perception of behaviour management techniques for paediatric patients among dental officers / Nor Asmawati Che Lah ... [et al.] - Che Lah, Nor Asmawati; Badrul Hisham, Abdul Rauf; Zakaria, Nurul Syahirah; Mohamad Jurimi, Nur Hazwani; Mohd Fathil, Naimah Hasnah; Mohamad, Farah Najihah; Leong, Kei Joe (Faculty of Dentistry, Universiti Teknologi MARA, 2024)
Introduction: Dental anxiety can be effectively managed by applying p harmacological and non-pharmacological behavioural management therapy approaches (BMT). This study investigated the dental officers’ perception of behaviour management techniques practiced in managing paediatric dental patients in primary dental clinics. Materials and methods: A quantitative study using structured online English questionnaires among dental officers serving in primary dental care services under the Ministry of Health Malaysia (MOH Malaysia) in Sabah. The acceptability of applied behaviour management techniques was measured using Likert scale from 0 to 10. Data was analysed using SPSS version 29 and descriptive data was presented. Results: Seventy-four d ental officers involved in this study (Male= 14, Female= 60). Positive verbal reinforcement, tell-show-d o, and offering an exact explanation of what the findings indicate are the most widely accepted behaviour management strategies (BMT), with mean scores o f 9.5, 9.1, and 8.7, respectively. The least accepted BMT among dental o fficers in Sabah are immobilisation with a papoose board, preventing the child from speaking during treatment, and hand over mouth (HOM), with mean scores of 4.6, 3.6, and 3.2, respectively. Conclusion: The study concludes that the most recognized BMT is positive reinforcement technique regardless of age, experience and gender. This finding p rovides information in the development of modules for continuous professional